2018
DOI: 10.1007/978-3-319-93885-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ecological Interface Design for Future ROV Capabilities in Maritime Command and Control

Abstract: Future maritime command teams will process more data, a trend driven by continued technological advances and new sensors. Remotely Operated Vehicles (ROVs) are contributing to this, as their usage is steadily growing in civilian and military contexts. A key challenge is effective integration of growing volumes of data into the command team, ensuring optimal performance for completing the variety of missions and tasks that may be required. In particular, operator cognitive capacity should not be exceeded, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…This is done by describing hierarchical means-ends relationships between process parameters. The approach has proven effective in shaping users' behaviors within system boundaries (i.e., a range of actions within which system goals are not violated) in a variety of application domains such as energy efficiency monitoring [13,14], maritime transport [9], aviation [4,8] and medical engineering [19,23]. In our previous work [40,41] we applied the WDA to the design of two VA interfaces which improved experts and novices' ability to understand complex situations in the domain of air traffic control.…”
Section: Related Workmentioning
confidence: 99%
“…This is done by describing hierarchical means-ends relationships between process parameters. The approach has proven effective in shaping users' behaviors within system boundaries (i.e., a range of actions within which system goals are not violated) in a variety of application domains such as energy efficiency monitoring [13,14], maritime transport [9], aviation [4,8] and medical engineering [19,23]. In our previous work [40,41] we applied the WDA to the design of two VA interfaces which improved experts and novices' ability to understand complex situations in the domain of air traffic control.…”
Section: Related Workmentioning
confidence: 99%
“…interfaces and also for resolving interface issues. In the context of EID, WDA has been performed to improve energy efficiency monitoring Jamieson, 2007, 2014), railway driving performance (Read et al, 2021), road (Baber et al, 2019) and maritime (Van Dam et al, 2006;Morineau et al, 2009;Fay et al, 2018) traffic management, medical engineering (Kwok and Burns, 2005;McEwen et al, 2012;Li et al, 2014), aviation (Amelink et al, 2005;Borst et al, 2007;Van Dam et al, 2008;Borst et al, 2008Borst et al, , 2010Ellerbroek et al, 2011Ellerbroek et al, , 2013 and in ATC (Lodder et al, 2011;Klomp et al, 2014;Mercado Velasco et al, 2015;Beernink et al, 2015;Borst et al, 2017;Ellejmi et al, 2018) In the context of resolving interface issues, Mumaw et al (2000a,b); Xu (2007) performed WDA and identified gaps and actions needed to resolve pilots' flight deck automation issues.…”
Section: Ecological Interface Designmentioning
confidence: 99%